The crucial roles of N6-methyladenosine (m6A) modification in the carcinogenesis and progression of colorectal cancer - Zhihao Fang (Cell & Bioscience, 2021)
Abstract As the predominant modification in RNA, N6-methyladenosine (m6A) has attracted increasing attention in the past few years since it plays vital roles in many biological processes. This chemical modification is dynamic, reversible and regulated by several methyltransferases, demethylases and proteins that recognize m6A modification. M6A modification exists in messenger RNA and affects their splicing, nuclear export, stability, decay, and translation, thereby modulating gene expression. Besides, the existence of m6A in noncoding RNAs (ncRNAs) could also directly or indirectly regulated gene expression. Colorectal cancer (CRC) is a common cancer around the world and of high mortality. Increasing evidence have shown that the changes of m6A level and the dysregulation of m6A regulatory proteins have been implicated in CRC carcinogenesis and progression. However, the underlying regulation laws of m6A modification to CRC remain elusive and better understanding of these mechanisms will benefit the diagnosis and therapy. In the present review, the latest studies about the dysregulation of m6A and its regulators in CRC have been summarized. We will focus on the crucial roles of m6A modification in the carcinogenesis and development of CRC. Moreover, we will also discuss the potential applications of m6A modification in CRC diagnosis and therapeutics.